A disclination model for twinning and de-twinning of nanotwinned copper. Issue 3 (22nd January 2016) - Xie, Chao; Fang, Qihong; Li, Luoxing; Chen, Jiankang; Zhang, Minghua; Liu, Youwen; Rolfe, Bernard
Abstract: The twinning and de-twinning processes within grains of nanotwinned copper (nt-Cu) are schematically demonstrated using the concept of wedge disclination quadrupoles. The stable twin nucleus size and the equilibrium equation of the applied shear stress and twin width during twin growth are obtained. The dependence of the critical resolved shear stress for twinning on the grain size, which conforms to the classic Hall–Petch relationship, is theoretically modelled. Additionally, the disclination quadrupole model for de-twinning is used to interpret the strength softening in nt-Cu. Relative to the classic kinetic and energetic models, this novel approach is more compatible with the experiments.